Pengaruh Kualitas Pelayanan dan Citra Perusahaan Terhadap Kepuasan Nasabah - Wati, Ni Nyoman; Putri Trarintya, Mirah Ayu; Putra Astawa, i Putu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
This study aims to partially and simultaneously influence service quality and corporate image on customer satisfaction at the Guwang Traditional Village LPD. The population in this study are all LPD customers in the Guwang Traditional Village in 2022 of 3,080 people. Determination of the sample using the Slovin formula so that 97 people were obtained as samples taken using the accidental sampling method. After testing the instrument and testing the classical assumptions, then the data was analyzed using multiple linear regression analysis. The results of the analysis show that service quality has a significant positive effect on customer satisfaction at the Guwang Traditional Village LPD. Corporate image has a significant positive effect on customer satisfaction in the Guwang Traditional Village LPD. Service quality and corporate image simultaneously have a significant positive effect on customer satisfaction at the Guwang Traditional Village LPD. It is suggested to the Guwang Traditional Village LPD to further improve the LPD waiting room facilities and prioritize customers in the Guwang Traditional Village to further advance the economy of the community around the LPD area.